TECHNIQUES, METHODS, AND IDEOLOGY IN THE TRANSLATION OF CULTURAL WORDS IN BBC NEWS - Janis Adi Wicaksono; Dwi Aji Prajoko (Humaniora Scientia, 2018)
This study discussed about the cultural words in the online news sites named BBC News. Itexplained also the techniques, methodes, and ideology choosen and applied by thetranslator. The data was collected from an online news site named BBC News and itstranslation. This research applied the descriptive-qualitative method. This research appliedalso the purposive sampling because the population of this study was too large. Thetechniques are used to analyze the data called as domain analysis, taxonomic analysis, andcomponential analysis. Then, for the result of all of analysis named as cultural themeanalysis. The finding of this research presented all of cultural words included in Newmarkâ€™sdescription. Some techniques employed to translate the cultural words, namely adaptation(14), addition (3), established equivalent (24), generalization (5), and pure borrowing (14).Addition is the least employed translation technique, but the most frequently is technique ofestablished equivalent. Then, the method which emphasis on the target language is choosen.In terms of ideology, the ideology of domestication is the ideology which is choosen andapplied by the translator.Keywords:Â  Translation, Cultural Words, Techniques, Methods, Ideology